2016
DOI: 10.1158/0008-5472.can-15-3268
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 Inhibition Reprograms Pancreatic Cancer Stem Cells via Upregulation of the miR-17-92 Cluster

Abstract: Pancreatic ductal adenocarcinoma (PDAC) and other carcinomas are hierarchically organized, with cancer stem cells (CSC) residing at the top of the hierarchy, where they drive tumor progression, metastasis, and chemoresistance. As CSC and non-CSC share an identical genetic background, we hypothesize that differences in epigenetics account for the striking functional differences between these two cell populations. Epigenetic mechanisms, such as DNA methylation, play an important role in maintaining pluripotency … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 48 publications
5
62
1
Order By: Relevance
“…Additionally, DIM’s novel functions of inducing pancreatic cancer cell differentiation, suppressing the expression of CD44, a pancreatic cancer stem cell (CSC) marker and a downstream target gene of KLF4 and then inhibiting the spheroid colony formation of pancreatic cancer cells are of clinical significance. These findings are also in line with a recent study showing that pancreatic CSCs expressed higher DNMT1 levels than non-CSC, and thus, had a higher level of DNA methylation; and pharmacologic or genetic targeting of DNMT1 in CSCs reduced their self-renewal and in vivo tumorigenic potential, defining DNMT1 as a candidate CSC therapeutic target (58). Given that pancreatic CSCs are mainly responsible for therapeutic resistance and relapse, our findings may help the development of novel anti-CSC strategies to improve the poor outcome of PDAC patients.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, DIM’s novel functions of inducing pancreatic cancer cell differentiation, suppressing the expression of CD44, a pancreatic cancer stem cell (CSC) marker and a downstream target gene of KLF4 and then inhibiting the spheroid colony formation of pancreatic cancer cells are of clinical significance. These findings are also in line with a recent study showing that pancreatic CSCs expressed higher DNMT1 levels than non-CSC, and thus, had a higher level of DNA methylation; and pharmacologic or genetic targeting of DNMT1 in CSCs reduced their self-renewal and in vivo tumorigenic potential, defining DNMT1 as a candidate CSC therapeutic target (58). Given that pancreatic CSCs are mainly responsible for therapeutic resistance and relapse, our findings may help the development of novel anti-CSC strategies to improve the poor outcome of PDAC patients.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have demonstrated that DNMT1 is required for maintenance of CSC in a variety of cancers, including prostate cancer, pancreatic cancer and breast cancer [22][23][24]. For instance, DNMT1 induces histone demethylation of H3K9me3 and H3K27me3 on the Zeb2 and KLF4 promoter in prostate cancer cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…DNA methyltransferase 1 (Dnmt1) is the most abundant DNA methyltransferase in somatic cells [1][2][3], and mediates the fidelity of CpG methylation patterns in newly generated daughter cells [3,4]. Loss of Dnmt1 is embryonically lethal with mouse embryonic stem cells lacking the catalytic function of Dnmt1 arresting prior to 10 the 8-somite stage [2] and complete knockout of Dnmt1 in cultured cells results in G2/M cell cycle checkpoint arrest followed by apoptosis [2,5]. Dnmt1 protein and its methyltransferase activity are required to maintain an undifferentiated and inexhaustible proliferative state in many stem cells and knockdown of Dnmt1 subsequently leads to premature differentiation of cells and eventually apoptosis as a result of loss of methylation markers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Dnmt1 protein and its methyltransferase activity are required to maintain an undifferentiated and inexhaustible proliferative state in many stem cells and knockdown of Dnmt1 subsequently leads to premature differentiation of cells and eventually apoptosis as a result of loss of methylation markers [6]. Increased abundance of Dnmt1 protein has been shown in several cancer types, and 15 typically correlates with tumour progression and altered genomic CpG methylation levels [7][8][9][10]. Dysregulated DNA methylation activity results in cancer-specific methylation-dependent suppression of targeted gene expression, acting in a similar way to mutations that adversely affect tumour suppressor genes in developing tumour cells [4,11,12].…”
Section: Introductionmentioning
confidence: 99%